A divulgação científica na página web do PPGEEC/UEA: contribuições para a educação científica - Mateus, Wagner de Deus (2013)
The Science Communication (DC) approach in Science Education emerges as a way of coping with impregnation scientific society to enhance development opportunities. And believe it or scientific information located in the online environment are products that can assist with this cultural growth, this paper aims to analyze the process of science communication done on the Internet, especially the web page of the Post-Graduate Education and Science Teaching in the Amazon State University of Amazonas (PPGEEC / UAS) as an agent that allows the development of Scientific Education. This is a qualitative and quantitative research with literature, systematic observation and use of checklist-based indicators of quality, usability evaluators and electronic online questionnaire to check the users' perception of the website. The indicators measured gave us notice that DC exists even in unspecified locations for such action, but there must be a information architecture for this process to be efficient and effective. And so the website of the Post-Graduate Education and Science Education in the Amazon State University of Amazonas (PPGEEC / UAS) can be considered an agent that enables the development of science education as socialization information and scientific research and technological society in a perspective of socio-educational inclusion. KEYWORDS: Science Divulgation. Internet.Websites.Science Education.Quality indicators.Grade ofEvaluation.